Panggilan Sebagai Guru Kristen Wujud Amanat Agung Yesus Kristus Dalam Penanaman Nilai Alkitabiah Pada Era Digital [A Christian Teacher’s Calling in Response to Jesus Christ’s Great Commission in Instilling Biblical Values in a Digital Era] - Jossapat Hendra Prijanto (Universitas Pelita Harapan, 2017)
The purpose of this paper is to discuss a Christian teacher’s calling in response to the great commission of Jesus Christ in building character in digital era. The main task of a teacher in the context of Christian education is to assist students in knowing God in Jesus Christ and being like Christ in their daily lives. Christian teachers become co-workers with God in conveying the values of His kingdom in a digital era that is filled with individualism, selfishness, and self-righteousness, all of which lead to the loss of love. The teaching that is delivered by Christian teachers can bring students to God’s truth which will affect students’ character, intellect, and spirituality. These not only help students but can also be used to serve and help other people to face the challenges of this digital era.BAHASA INDONESIA ABSTRAK: Tulisan ini bertujuan untuk membahas panggilan guru Kristen sebagai wujud amanat agung Yesus Kristus dalam penanaman nilai pada era digital. Tugas utama seorang guru dalam konteks pendidikan Kristen adalah membantu para siswa untuk belajar mengenal Allah di dalam Yesus Kristus dan melalui firmanNya. Mereka dapat menjadi serupa dengan Kristus dalam kehidupan sehari-hari. Oleh sebab itu penting sekali mahasiswa menangkap panggilanNya sebagai Guru Kristen, karena dengan demikian akan menjadi rekan sekerja Allah dalam menyampaikan nilai-nilai kerajaanNya di era digital yang sarat dengan egoisme, mementingkan diri sendiri, bahkan merasa diri benar, sehingga kasih menjadi pudar. Dengan demikian, pengajaran yang disampaikan guru Kristen akan membawa para siswa memiliki nilai-nilai kebenaran yang justru kembali kepadaTuhan dan berpusat kepada Kristus, yang berdampak kepada pertumbuhan karakter intelektual, spiritual, intelegensi tidak hanya menjadi kebanggaan sendiri melainkan dipakai untuk melayani dan menolong orang lain dalam menghadapi era digital ini.